Perception and willingness toward various immunization routes for COVID-19 vaccines: a cross-sectional survey in China - Wang, Haohang; Cui, Mingting; Li, Shunran; Wu, Fan; Jiang, Shiqiang; Chen, Hongbiao; Yuan, Jianhui; Sun, Caijun (Frontiers in Public Health, 2023)
Background To date, most vaccines, including the COVID-19 vaccine, are mainly administered by intramuscular injection, which might lead to vaccine hesitancy in some populations due to needle fear. Alternatively, needle-free immunization technology is extensively developed to improve the efficacy and acceptance of vaccination. However, there is no study to report the perception and willingness toward various immunization routes of the COVID-19 vaccine in the general population. Methods A cross-sectional survey was conducted nationwide using an online questionnaire. Bivariate analyses were undertaken to assess variable associations among the participants who reported a hesitancy to receive the COVID-19 booster vaccination. Multivariable logistic regression with a backward step-wise approach was used to analyze the predicted factors associated with the willingness to receive the COVID-19 booster vaccination. Results A total of 3,244 valid respondents were included in this survey, and 63.2% of participants thought they had a good understanding of intramuscular injection, but only 20.7, 9.2, 9.4, and 6.0% of participants had a self-perceived good understanding of inhalation vaccine, nasal spray vaccine, oral vaccine, and microneedle patch vaccine. Correspondingly, there was high acceptance for intramuscular injection (76.5%), followed by oral inhalation (64.4%) and nasal spray (43.0%). Those participants who were only willing to receive an intramuscular vaccine had less vaccine knowledge (OR = 0.78; 95% CI: 0.65–0.94) than those who were willing to receive a needle-free vaccine (OR = 1.97; 95% CI: 1.52–2.57). Some factors were found to be associated with vaccine hesitancy toward booster COVID-19 vaccination. Conclusion Needle-free vaccination is a promising technology for the next generation of vaccines, but we found that intramuscular injection was still the most acceptable immunization route in this survey. One major reason might be that most people lack knowledge about needle-free vaccination. We should strengthen the publicity of needle-free vaccination technology, and thus improve the acceptance and coverage of vaccination in different populations.